Penggunaan Algoritma Clustering K-means Untuk Melihat Daerah-Daerah Penyuplai Mahasiswa Di Universitas Kristen Satya Wacana, Salatiga. - Rivort Pormes; Daniel H. F. Manongga (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
The use of k-means algorithm in student supply process is done to see students supply tendency in each region who study at satya wacana christian university (SWCU). This data processing with k-meansis useful for extracting information and knowledge from students data at SWCU. With data mining processing, the stakeholders at SWCU can take strategic steps for the penetration process in regions with potential student supply indication. The use of k-meansalgorithms facilitates the process of data analysis as well as grouping on student data during a 5-year period. The aim of this study is to provide on target strategic picture for regions which potentially have a significant impact on students supply each year.